Peningkatan Kapasitas Kelembagaan Nelayan - -, Hidayat - (Citra Lekha, 2013)
The fisherman’s institutional has strategic dimension both for empowering fisherman community to do sustainable development of marine resources and to increase their independence and welfare. This institution has normative positions to serve as guidelines to be and behave in social relations and interaction in line with the socio-cultural and ecological environment. While the function of this institution is being regulativerules related to household subsistence, integration, and social control. With these functions, they may determine their manners, capacities, and their autonomy to fulfill life’s necessities, standard of living and culture. So this is also can be called "hidden insurance" and "social energy" to survive their problems of life and society. The strategic role has to be empowered, integrated and synergized, both at the level of individual, organizational, through regulation of human resources, business opportunities, improvement of governance, ecology, and marine resources.Abstract: institution, empowered, marine resources, sustainable development.